Peningkatan Kapasitas Dalam Teknologi Pakan Dan Pengolahan Limbah Ternak Pada Kelompok Peternak Sapi Potong Di Desa Mattirowalie, Kec. Libureng, Kab. Bone - Said, Muhammad Irfan; Hatta, Muhammad; Rohani, St. (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2018)
Knowledge of animal feed and waste is an important component in building the livestock industry. The aspectof availability of feed and the production of livestock waste is one of the problems by cattle farmers in MattirowalieVillage, Libureng Sub-District, Bone Regency. Efforts to increase the capacity of farmers in solving these problems areneeded to increase the productivity of their livestock. This program aims to increase knowledge for farmers of beef cattlein processing agricultural and livestock waste into feed products and processing them into organic fertilizer. This activityis an implementation of the Program Pengabdian Kepada Masyarakat Unhas (PPMU) Program Kemitraan Masyarakat(PKM). This activity was carried out in Mattirowalie Village, Libureng Sub-District, Bone Regency. The partner groupsinvolved as targets were the "Kurusumange" and "Masempo Dalle" farmers group (FG). The number of trainingparticipants involved in this activity is approximately 25 peoples, overall were cattle farmers with 2-3 cattle/person. Theimplementation of technology introduction programs was carried out in the form of training programs and technologyassistance. Several technology packages that have been implemented were: 1) ammoniation technology, 2) complete feedsilage fermentation technology, 3) manufacturing of local microorganism (LM) technology and 4) Urea Molasses Block(UMB) manufacturing technology. The results of the implementation of activities to increase the capacity of partnermembers in processing agricultural waste and livestock into alternative animal feed and organic fertilizer